Site-specific transgenesis by Cre-mediated recombination in Drosophila - Oberstein, Adam; Pare, Adam; Kaplan, Leah; Small, Stephen (Nature methods, 2005)
Transposons such as P elements are routinely used to stably transfer exogenous DNA (transgenes) into the Drosophila genome. Transgene insertion events, however, are essentially random and are subject to 'position effects' from nearby endogenous regulatory elements. Here we describe a microinjection-based system that uses Cre-mediated recombination to insert transgenes into precise genomic 'landing sites'. The system is simple and efficient, and will permit precise comparisons between multiple transgenic constructs.